Stem Cells, Including a Population of Very Small Embryonic-Like Stem Cells, are Mobilized Into Peripheral Blood in Patients After Skin Burn Injury - Drukała, Justyna; Paczkowska, Edyta; Kucia, Magda; Młyńska, Elżbieta; Krajewski, Andrzej; Machaliński, Bogusław; Madeja, Zbigniew; Ratajczak, Mariusz Z. (Stem cell reviews, 2012)
Background Developmentally early cells, including hematopoietic stem progenitor cells (HSPCs), as well as very small embryonic-like stem cells (VSELs), are mobilized into peripheral blood (PB) in response to tissue and organ injury (e.g., heart infarct or stroke). Objective We seek to determine whether these cells are also mobilized into PB in patients with skin burn injuries. Methods Forty-four (44) patients (33–57 years of age) with total body surface burn area of 30–60%, as well as 23 healthy control subjects, were recruited and PB samples were harvested during the first 24 hours, day +2, and day +5 after burn injury and compared to normal controls. The circulating human CD34 + CD133 + cells enriched for HSPCs, as well as small CXCR4 + CD34 + CD133 + subsets of Lin – CD45 – cells that correspond to the population of VSELs, were counted by FACS and evaluated by direct immunofluorescence staining for pluripotency markers (Oct-4, Nanog, and SSEA-4). In parallel, we also measured by ELISA the serum concentration of factors that regulate stem cell trafficking, such as SDF-1, VEGF, and HGF. Results Our data indicate that skin burn injury mobilizes cells expressing stem cell-associated markers, such as CD133, CD34, and CXCR4, into PB. More importantly, we found an increase in the number of circulating primitive, small Oct-4 + Nanog + SSEA-4 + CXCR4 + lin – CD45 – VSELs. All these changes were accompanied by increased serum concentrations of SDF-1 and VEGF. Limitations Further studies are needed to fully assess the role of mobilized stem cells in the healing process to see if they can contribute to skin regeneration. Conclusion Skin burn injury triggers the mobilization of HSPCs and CXCR4 + VSELs, while the significance and precise role of mobilized VSELs in skin repair requires further study.